A Self-Regulated Learning Perspective on Smartphone Presence, Usage, and Multitasking While Studying - Bridget K. Daleiden; Kendall Hartley; Lisa D. Bendixen (Education Sciences)
The implications of the presence and usage of smartphone technology in learning contexts are not fully understood. Self-regulated learning (SRL) theory offers a framework in which smartphone use can be explored. The current study seeks to extend our understanding of the role of the smartphone while studying through a qualitative thematic analysis of responses to open-ended questions regarding smartphone use. A sample of 210 college students responded to questions about their smartphone use and multitasking behavior while studying. The findings indicate that college students use smartphones while studying to communicate, find information, and entertain themselves by media multitasking with their smartphones.